"You are young and can afford to do something stupid": fostering an understanding of electronic spin in chemistry - Joyce, Justin P., author; Shores, Matthew P., advisor; Rappé, Anthony K., advisor; Neilson, James R., committee member; Reynolds, Melissa M., committee member; Ross, Kathryn A., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
You are young and can afford to do something stupid: fostering an understanding of electronic spin in chemistry
Keywords: electronic spin; Pauli Exclusion; wavefunction; electronic structure; bioinorganic chemistry